Community Participation in Festival and Digital Tourism Campaign (Case of North Halmahera District, Indonesia) - Singgalen, Yerik Afrianto; Sasongko, Gatot; Wiloso, Pamerdi Giri (Graduate School, Universitas Brawijaya, 2019)
Galela community participation in the implementation of the Festival Tanjung Bongo (FTB) shows the existence of a partnership pattern in accordance with pentahelix elements. This research uses qualitative method with case study approach to describe the level of local community participation in preparation of Festival activities and various dynamics that occur in realizing these activities. An in-depth interviews, observation and document studies were implemented in order to generate data. The triangulation techniques were implemented as data validation techniques to obtain credible information. The results of this study indicate that the local government becomes a stimulus for community participation in the planning and preparation stage of the Tanjung Bongo Festival event, although the activity was postponed due to the refusal from the National League for Democracy (LMND eks) executives related to the readiness of supporting infrastructure. On the other hand, the pentahelix element of government synergy, academic, association, community and media becomes the very essential factors in organizing the festival. Meanwhile, the level of community participation can be categorized to achieve the level of citizen control in accordance with Arnstein (1969).Keywords: Digital Campaign, North Halmahera, Participation, Pentahelix, Tanjung Bongo Festival.